On the question of the formation of associations of hotel companies in the global hospitality industry - Ussenova , D.M. (BUKETOV BUSINESS REVIEW, 2017)
The hotel service industry plays an important role in society, providing opportunities for business meetings, meetings, conferences, as well as for recreation and entertainment. This trend of hotel development creates objective conditions for the so-called regional competition, which every year it becomes more noticeable: new resorts with inflated standards of service that makes the old tourism regions to improve their quality of service, as well as look for new ways of quality competition. For this reason the article discusses the main aspects of the development of hotel associations and the most famous and developed hotel brands in the market of hotel services. Special attention is paid to the integration processes in the global hotel market, forms of association of hotels as the franchise agreement, contract to manage, combination of franchising and contract to manage, an agreement to acquire a license, strategic marketing alliances. Questions of franchising system in the world hotel market are considered, and the structure of the model franchise payments for hotel companies are defined. In the article the advantages and disadvantages of franchising for the franchisor are highlighted.